Game-Based STEM Learning for Enhanced Engagement: A Collaborative Program Involving Teachers, Students, and Parents - Woro Sri Hastuti; Fery Muhamad Firdaus; Yeni Rakhmawati; Rahayu Condro Murti; Dewi Agus Damayanti; Sefta Andrea Putri Hutauruk (Engagement: Jurnal Pengabdian Kepada Masyarakat, 2026)
Background: Limited access to educational technology at Sekolah Indonesia Yangon (SIY), Myanmar, created challenges in implementing engaging STEM learning. This community service program addressed these issues by supporting teachers, students, and parents in adopting creative, low-cost STEM activities. Purpose of the Study: The program aimed to enhance teachers’ competence in game-based STEM learning, improve students’ STEM concept mastery, and strengthen parental involvement in home-based learning within a three-month period. Methods: A participatory mentoring model was used, integrating game-based learning, collaborative workshops, and hands-on experimentation through the activity “Ice Cream without a Freezer.” Pre- and post-evaluations assessed changes in teacher skills, student understanding, and parental engagement. Results: The program increased students’ STEM understanding by 33%, improved teachers’ creativity in designing learning games, and encouraged stronger parental support. The activity effectively fostered collaboration, communication, creativity, and problem-solving skills using simple, low-cost materials.